Pseudomonas aeruginosa inhibits the growth of Scedosporium aurantiacum, an opportunistic fungal pathogen isolated from the lungs of cystic fibrosis patients - Kaur, Jashanpreet; Pethani, Bhavin P.; Kumar, Sheemal; Kim, Minkyoung; Sunna, Anwar; Kautto, Liisa; Penesyan, Anahit; Paulsen, Ian T.; Nevalainen, Helena (Frontiers in Microbiology, 2015)
The filamentous fungus Scedosporium aurantiacum and the bacterium Pseudomonas aeruginosa are opportunistic pathogens isolated from lungs of the cystic fibrosis (CF) patients. P. aeruginosa has been known to suppress the growth of a number of cystic fibrosis related fungi such as Aspergillus fumigatus, Candida albicans and Cryptococcus neoformans. However, the interactions between P. aeruginosa and S. aurantiacum have not been investigated in depth. Hence we assessed the effect of P. aeruginosa reference strain PAO1 and two clinical isolates PASS1 and PASS2 on the growth of two clinical S. aurantiacum isolates WM 06.482 and WM 08.202 using solid plate assays and liquid cultures, in a synthetic medium mimicking the nutrient condition in the CF sputum. Solid plate assays showed a clear inhibition of growth of both S. aurantiacum strains when cultured with P. aeruginosa strains PASS1 and PAO1. The inhibitory effect was confirmed by confocal microscopy. In addition to using chemical fluorescent stains, strains tagged with yfp (P. aeruginosa PASS1) and mCherry (S. aurantiacum WM 06.482) were created to facilitate detailed microscopic observations on strain interaction. To our knowledge, this is the first study describing successful genetic transformation of S. aurantiacum. Inhibition of growth was observed only in co-cultures of P. aeruginosa and S. aurantiacum; the cell fractions obtained from independent bacterial monocultures failed to initiate a response against the fungus. In the liquid co-cultures, biofilm forming P. aeruginosa strains PASS1 and PAO1 displayed higher inhibition of fungal growth when compared to PASS2. No change was observed in the inhibition pattern when direct cell contact between the bacterial and fungal strains was prevented using a separation membrane suggesting the involvement of extracellular metabolites in the fungal inhibition. However, one of the most commonly described bacterial virulence factors, pyocyanin, had no effect against either